Up Scaling Invasive Plant Biomass Briquette Production: Case of Kendu Bay, Lake Victoria, Kenya - Rodrigues, Anthony Joachim; Odero, Martin Omondi; Kerich, Daniel; Odundo, Francis; Akuno, Walter (Advances in Social Sciences Research Journal, 2017)
Simple, production processes involving local community labour provide useful cottage fuel products. Such conversion of waste or intrusive bio mass to fuel briquettes is more about know-how than large capital infrastructure and funding. This paper describes up scaling a pilot process that converted water hyacinth to briquettes by hands on training of Kendu Beach Community Unit members, in situ, over a two week period. System and target knowledge, before training, and transformational knowledge, post training, were elicited and the results analyzed. Briquettes produced from five plant bio mass types and their respective blends vide carbonization, were tested in a laboratory. Water hyacinth briquettes produced during up scaling were much better than those produced during the pilot production due to machine compaction refinements. Blending five dried biomass types with each other before carbonization yielded higher calorific values despite the labour intensive and relatively low technology mediated process. User acceptance tests were conducted on site. The uptake of the easy to follow; labour intensive process using simple briquetting machines was a success with the community producing briquettes on their own after an initial three day, post drying production run. Such cottage solutions for domestic consumption and sale should be promoted as a sustainable substitute for fossil or wood based fuel. Confidence building measures between the community and their devolved representatives such as ward administrators and members of Constituent Assemblies under the 2012 Constitutional dispensation should be undertaken. The East African Community project LVEMP-II should, through greater stakeholder engagement, have a greater impact on Lake Victoria’s ecosystem in order to enhance the livelihoods of the beach communities.